The calorimetric inestigation of fusions of the system Ni–O and Ni–O–M - Шаркіна, Н.О.; Ільчак, О.Б.; Федорчак, Т.О. (Proceedings of National Aviation University (archive), 2010)
The enthalpy of mixing of fusions of the system Ni - O - M (M - IVb -, Vb, - VIb are metals) is studied by the calorimetric method at Т = 1780 K. Shown that the partial enthalpy of mixing for all studied systems are minus quantity. D`Ні of these fusions is confirmed by data got by E.M.F. method with a hard oxide electrolyte.